Immunization Coverage and Associated Factors in Aceh Indonesia - Iin Nurlinawati; Mukhlissul Faatih (Universitas Islam Bandung, 2022)
Few studies have looked into why global immunization coverage has plummeted, particularly in Indonesia. The Indonesian government had a childhood immunization program including in Aceh. This study aimed to learn more about immunization coverage in Aceh, Indonesia, and the factors that influence it. This cross-sectional study relied on data from the National Basic Health Surveys conducted in 2013 and 2018. The children in this study ranged in age from 12 to 23. The coverage of vaccines in Aceh fell by 50% between 2013 and 2018. (38.3% to 19.5%, the lowest in Indonesia). The number of children in Aceh who did not receive immunizations increased by 100%. (19.8% to 40.9%). While the percentage of children who have not received their complete vaccination has decreased by 5% (41.9% to 39.56%). The characteristics of the head of household with unvaccinated children were largely poor education, and the majority came from the poorest quartile of wealth. The most common reasons for refusal were families' refusal to allow immunization (43%) and fear of post-immunization fever (32%). Unvaccinated children come from low-income, low-educated families who refuse immunization.